Collaborative Management to support sustainable Community Forest. Issue 1 (1st January 2023) - Yatim, Hertasning; Yusran, Yusran; Supratman,; Zaman, Nur
Abstract: The current state of social forestry, including community forestry (HKm) in Indonesia, is practically stagnant. Many factors cause stagnation in HKm management, including the main one being the interaction with the Forest Management Unit (FMU) as forest manager at the site level. This study aims to build an institutional model for sustainable forest management through analysis of the arena of action, community attributes, and forest management rules at the Nambo Community Forest, Central Sulawesi. The results of this research found that the collaborative management model between the government and the community is suitable to be applied in Community Forest management, because it provides greater opportunities for recognizing the rights of local communities to forest resources, as well as increasing the empowerment of rural communities.